2018
DOI: 10.1002/hec.3644
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation or recovery after health shocks? Evidence using subjective and objective health measures

Abstract: In this paper, we analyse the effect of an onset of a health shock on subjective survival probability and compare it with objective survival probability and self-reported health measures. In particular, we are interested in whether expectations of people respond to health shocks and whether these follow the evolution of objective life expectations and self-reported health measures over time. Using longitudinal data from the Health and Retirement Study, we estimate fixed effects models of adaptation for the obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Lindeboom and van Doorslaer, 2004;Johnston et al, 2009). We also find an indication of a U-shaped relationship between age and self-assessed health (for similar findings see Johnston et al, 2009;Baji and Bíró, 2018). Employed individuals and those with higher income report better health as do those with secondary and higher education (relative to individuals with no education).…”
Section: Baseline Resultssupporting
confidence: 77%
“…Lindeboom and van Doorslaer, 2004;Johnston et al, 2009). We also find an indication of a U-shaped relationship between age and self-assessed health (for similar findings see Johnston et al, 2009;Baji and Bíró, 2018). Employed individuals and those with higher income report better health as do those with secondary and higher education (relative to individuals with no education).…”
Section: Baseline Resultssupporting
confidence: 77%
“…1). Adaptation to deteriorating health with age might be one explanation of this difference [40]. We found strong correlations between the EQ-5D-3L and EQ-5D-5L-based SHE results indicating that good estimates can be calculated from one to another in case of lack of available data.…”
Section: 219mentioning
confidence: 69%
“…Therefore, a possible reason for adaptation may be misperceptions of people regarding their actual health status after the diagnosis of a disease. This is supported by the study by Baji and Bíró [62], who compared the effects of health shocks on subjective and objective survival probabilities. They found that some people are overly optimistic about their actual health condition and are not always fully aware of the negative long-term consequences of health shocks.…”
Section: Potential Mechanismsmentioning
confidence: 70%